Proses Metakognisi Mahasiswa Dalam Memecahkan Masalah Matematika (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2018)
Kesadaran siswa tentang proses berpikirnya sendiri sangat penting dalam pemecahan masalah. Penelitian ini merupakan penelitian studi kasus yang bertujuan untuk mendeskripsikan proses metakognisi siswa dalam memecahkan masalah matematika. Pemilihan subjek didasaran pada keunikan subjek dalam menyelesaiakan masalah dan adanya gejala selalu memikirkan kembali apa yang dipikirkannya. Hasil penelitian menunjukkan bahwa proses metakognisi yang dialami subjek terdiri dari metacognitive awareness, metacognitive evaluation, dan metacognitive regulation.Â Students awareness of his own thinking process is important in problem solving. This study is a case study research that aims to describe the process of metacognition of students in solving mathematical problems. Subject was selected based on the uniqueness of the subject in solving the problem and the symptoms taht are always rethinking what he thinks. The results showed that the metacognition process experienced by the subject consists of metacognitive awareness, metacognitive evaluation, and metacognitive regulation.